Work scheduling through communication tools and job satisfaction: The roles of work-family conflict and perceived work pressure - Zhengxiu Sun; Senhu Wang; Yaguang Yan; Hong Tan; Shuangshuang Song; Shuanglong Li (PLoS ONE, 2026)
The expansion of digital communication has increasingly blurred the boundaries between work and personal life, making work scheduling through communication tools more common. In China, mobile platforms such as WeChat are widely used to facilitate work-related scheduling and coordination, allowing work instructions and messages to be communicated without being confined to fixed time periods. Using nationally representative data from the 2021 China General Social Survey (CGSS), this study examines the association between communication-tool-mediated work scheduling and employees’ job satisfaction. We use multiple linear regression models to assess whether respondents’ work could be scheduled at any time via WeChat or phone and whether this workplace practice is associated with job satisfaction. Then, we further examine the mediating roles of work–family conflict and perceived work pressure using the KHB method, and conduct supplementary subgroup analyses by socioeconomic status (SES). The results show that work scheduling through communication tools is negatively associated with job satisfaction, and that this relationship is largely mediated by higher levels of work–family conflict and perceived work pressure. In addition, SES-based subgroup regressions provide suggestive evidence that this negative association is mainly observed among individuals with higher educational attainment and those in professional occupations. These findings document how work scheduling through communication tools is related to employees’ subjective evaluations of work and highlight heterogeneity in these associations across socioeconomic groups in contemporary Chinese workplaces.